Modelo fractomecánico de propagación suscritica de fisura utilizando el método de elementos finitos - Angeles Reyes, Joseph Hernán (2013)
The industrial development at the world-wide level has experienced remarkable advances in the last years with respect to the Technology of Materials and it shows to the great meaning and importance to us that have metals specially the steel and their alloys using for the construction and manufacture of machineries, equipment, pieces and elements of machines._x000D_ At the present time the Physicists who work in the area of Materials have knowledge, that all the materials present/display own defects of their process of manufacture, like for example: vacancies, break-ups, pores, non-metallic inclusions and fissures; being the fissures the critical defects but, since these act like tension concentrators, arriving to propagate and to cause a catastrophic fracture, under applied conditions of load, inferior to those of design._x000D_ In the study of fault analysis this being developed a very important area that it is the Fractomecánico design attended by computer, which uses software specialized to simulate the Sub critical propagation of fissures as well as the catastrophic faults with a good approach with respect to the real data._x000D_ This work analyzes the approach in the determination of the parameters of sub critical propagation of fissure, using numerical methods, and making use for this, of software specialized, in a structural steel AISI 1045 previously tried in the laboratory by other investigators._x000D_ x_x000D_ The finite element analysis is a numerical method used to predict the behaviour of the materials in the presence of forces, discharges temperatures, vibration, etc. In terms of fracture as much caused as produced in the work of design._x000D_ The analysis was made using the finite elements analysis method by Autodesk ALGOR Simulation program. This program was used for determinate the material's KIC, using the library of materials from program Autodesk ALGOR Simulation program, for the steel AISI 1045 cold drawn 19-32mm, obtaining as result a value of 37,8 Kg/m1/2 compared with the 34,2 Kg/m1/2 value obtained by the investigators in the lab for structural steel Boholer H. Generating an error of about 10%. Modelling the test in two dimensions. Also was determined the most critical points and the maximum tension’s distribution, the compression’s tensions, the deformations and other parameters